Ионосферные эффекты магнитосферных электрических полей по наблюдениям на радаре некогерентного рассеяния в Харькове - Григоренко, Е. И.; Пазюра, С. А.; Таран, В. И.; Черногор, Л. Ф. (НТУ "ХПИ", 2004)
Effects of magnetosphere electric fields during geomagnetic storms are studied from the results of ionosphere observations with the Kharkov incoherent scatter radar. It is shown, that electric field pulse in the ionosphere over Kharkov, associated with the non-stationary magnetosphere electric fields and its penetration in the middle latitudes resulted in destabilizing of F region behavior during the severe magnetic storm on May 30,2003 and caused the anomalous ionosphere storm on March 21,2003
Keywords: радар HP; плазмосфера; солнечный ветер; магнитные бури; геомагнитная активность; солнечные бури; геофизические условия